Newborn care practices and home-based postnatal newborn care programme - Mewat, Haryana, India, 2013 - Latika Nath Sinha; Prabhdeep Kaur; Rakesh Gupta; Suresh Dalpath; Vinod Goyal; Manoj Murhekar (World Health Organization Regional Office for the Western Pacific, 2014)
Background: In India, the Home Based Postnatal Newborn Care programme by Accredited Social Health Activists (ASHAs) under the National Rural Health Mission was initiated in 2011 to reduce neonatal mortality rates (NMRs). ASHAs get cash incentives for six postnatal home visits for newborn care. We studied newborn care practices among mothers in Mewat, Haryana, having a high NMR and determined risk factors for unsafe practices and described the knowledge and skills of ASHAs during home visits. Methods: A cross-sectional survey was conducted among mothers who had delivered a child during the previous seven months using cluster sampling. We interviewed mothers and ASHAs in the selected subcentres using semi-structured questionnaires on the six safe newborn care practices, namely safe breastfeeding, keeping cord and eyes clean, wrapping baby, kangaroo care, delayed bathing and hand washing. Results: We interviewed 320 mothers, 61 ASHAs and observed 19 home visits. Overall, 60% of mothers adopted less than three safe practices. Wrapping newborns (96%) and delayed bathing (64%) were better adopted than cord care (49%), safe breastfeeding (48%), hand washing (30%), kangaroo care (20%) and eye care (9%). Cultural beliefs and traditional birth attendants influenced the mother's practices. The lack of supervision by auxiliary nurse midwives (ANM), delayed referral and transportation were the other challenges. Conclusion: Knowledge-practice gaps existed among mothers counselled by ASHAs. Poor utilization of reproductive and child health services decreased opportunities for ASHA-mother dialogue on safe practices. Recommendations included training ANMs, training TBAs as ASHAs, innovative communication strategies for ASHAs and improved referral system.